2018
DOI: 10.11144/javeriana.uo36-77.aeco
|View full text |Cite
|
Sign up to set email alerts
|

Análisis de los eventos desfavorables como resultado de la atención en cirugía oral

Abstract: Antecedentes: La cirugía oral es una especialidad que requiere preparación teórica y habilidad quirúrgica para efectuar los procedimientos. Durante el proceso de aprendizaje, los estudiantes, al efectuar cirugías, pueden enfrentar dificultades que dañen involuntariamente al paciente. A pesar de cumplirse los protocolos, es posible que se presenten eventos desfavorables durante la atención. Por este motivo, es necesario caracterizar y analizar dichos eventos en instituciones como una facultad de odontología par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…A study conducted in Argentina found that 49% of reports of these events in public and private settings occurred in this specialty, 9 many of them by inaccurate planning or inadequate management of technique. Another study with information from the graduate clinics of Pathology and Oral Surgery at a university in Bogotá, Colombia, 26 found a proportion of 7% of events listed as unfavorable. It is important for future analyses to make more detailed descriptions of the events, as well as possible causes and their corresponding managements.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in Argentina found that 49% of reports of these events in public and private settings occurred in this specialty, 9 many of them by inaccurate planning or inadequate management of technique. Another study with information from the graduate clinics of Pathology and Oral Surgery at a university in Bogotá, Colombia, 26 found a proportion of 7% of events listed as unfavorable. It is important for future analyses to make more detailed descriptions of the events, as well as possible causes and their corresponding managements.…”
Section: Discussionmentioning
confidence: 99%